Navigating Community and Place Through Colloquial Street Names in Fingo Village, Makhanda (Grahamstown) - Irvine, Philippa Margaret; Memela, Sinenhlanhla; Dlongolo, Zandile Nombulelo; Kepe, Thembela (Urban forum (Johannesburg), 2021)
Toponyms can be conceptualised as both symbolic capital and symbolic resistance – as means to express hegemonic power or to resist it. They have been cast as a means of transformation and restitution in the post-apartheid landscape of South Africa. The naming and renaming process has, therefore, been seen as a political act of representation and part of the nation-building project. These official names and official naming processes are only one layer of the toponymic landscape, however. There exists, parallel to these official names, the world of colloquial names which are used to express the history, landscape, politics and identity of local settlements and communities. The present research has given focus to the phenomenon of colloquial street names in Fingo Village in Makhanda (Grahamstown). Colonial and apartheid era names remain as the official toponyms on maps and street signs, but the community has developed colloquial names in parallel to them. The findings suggest that these names are organic in origin, express local identity and landscape, allow for everyday navigation and are inherited over generations, even as there is not always consensus on some of their origins and meanings. They serve as symbolic capital in delimiting the local community – defining insiders and outsiders. They can be seen as symbolic resistance inasmuch as they implicitly challenge the imposed official names.